2017
DOI: 10.3892/or.2017.5495
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the CRABPII/RAR pathway by curcumin induces retinoic acid mediated apoptosis in retinoic acid resistant breast cancer cells

Abstract: Due to the anti-proliferative and anti-apoptotic effects of retinoic acid (RA), this hormone has emerged as a target for several diseases, including cancer. However, development of retinoid resistance is a critical issue and efforts to understand the retinoid signaling pathway may identify useful biomarkers for future clinical trials. Apoptotic responses of RA are exhibited through the cellular RA-binding protein II (CRABPII)/retinoic acid receptor (RAR) signaling cascade. Delivery of RA to RAR by CRABPII enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 58 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…One approach to overcoming the resistance of tumor cells to retinoic acid may be genomic and epigenomic reprogramming, targeting and suppressing this pathway using markers that have been shown to restore sensitivity to retinoic acid [ 44 ]. For example, curcumin has been shown to restore sensitivity to retinoic acid in TNBC cells [ 44 ], and to induce retinoic mediated apoptosis in retinoic acid resistant breast cancer cells [ 45 ]. Moreover, DNA methylation investigated here has been shown to predict the response of TNBC to all-trans retinoic acid [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…One approach to overcoming the resistance of tumor cells to retinoic acid may be genomic and epigenomic reprogramming, targeting and suppressing this pathway using markers that have been shown to restore sensitivity to retinoic acid [ 44 ]. For example, curcumin has been shown to restore sensitivity to retinoic acid in TNBC cells [ 44 ], and to induce retinoic mediated apoptosis in retinoic acid resistant breast cancer cells [ 45 ]. Moreover, DNA methylation investigated here has been shown to predict the response of TNBC to all-trans retinoic acid [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…All-trans retinoic acid (RA) is well known as an anti-IBD and anti-tumor agent in clinical 22,23,[40][41][42][43] . Hong et al reported that RA attenuates experimental colitis through inhibiting NF-κB activation, however, its mechanism is very unclear 23 .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that triggering apoptosis in cells that are non-responsive to death receptor agonists or chemotherapeutics is challenging [ 48 ]. Therefore, it is of great interest to identify or develop active agents that overcome such resistances [ 49 , 50 , 51 , 52 ]. The observations showing that curcumin in combination with UVA-boosted H 2 O 2 generation indicated that a shift in the cellular redox balance might elicit the observed pro-apoptotic processes as also observed by others [ 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%